Prevalence of Depressive Symptoms Among University Students in Pakistan: A Systematic Review and Meta-Analysis - Khan, Muhammad Naeem; Akhtar, Parveen; Ijaz, Saira; Waqas, Ahmed (Frontiers in Public Health, 2021)
Background: In Pakistan, almost 30% population is between 15 to 29 years of age, with university enrollment rates of 10-15%. Although there is a growing concern on mental health of university students across the globe, studies from low and middle income countries such as Pakistan are scarce. We conducted a systematic review and meta-analysis of prevalence of depressive symptoms among Pakistani university students Methods: PubMed, Web of Science, PsycInfo and Google Scholar were searched between 15 to 30th January 2020. Cross-sectional and longitudinal studies, published till 31st December 2019 were included. Data on study characteristics and prevalence of depressive symptoms were extracted. Meta-analysis was conducted using random effects models. To estimate subgroup difference based on study characteristics, meta-regression and sub-group analyses were conducted. Results: In total, 26 studies involving 7652 participants were included in review. Overall prevalence of depressive symptoms was 42.66% (95% CI: 34.82% to 50.89%), with significant heterogeneity among studies. Subgroup analyses revealed a significant difference in prevalence estimates based on depression screening instrument and study major. Statistically significant differences were observed among studies employing different psychometric scales ((test for subgroup differences, Q = 21.92, p <0.05) and between students from different study majors (test for subgroup differences, Q = 3.76, p=0.05). Conclusion: Our study found that overall prevalence of depressive symptoms among university students in Pakistan was 42.66%, however, findings should be interpreted with caution. Large scale epidemiological surveys using valid and reliable tools are needed to better estimate prevalence of depression among Pakistani university students.